Directed Innovation of Business Models - Stelian Brad; Emilia Brad (International School for Social and Business Studies, 2016)
Business model innovation is an important issue to keep business competitive and increase company's profits. Due to many market attractors, identification of appropriate paths of business model evolution is a painful and risky process. To improve decision's effectiveness in this process, an architectural construct of analysis and conceptualization for business model innovation that combines directed evolution and blue ocean concepts is proposed in this paper under the name of directed innovation. It displays the key points where innovations would happen to direct adaptation of the business model towards sustainable competitiveness. Formulation of mature solutions is supported by inventive problem solving tools. The significance of the directed innovation approach is demonstrated in a case study dealing with business model innovation of a software company.